Comparative Analysis of the Enzymatic, Coagulant, and Neuromuscular Activities of Two Variants of Crotalus durissus ruruima Venom and Antivenom Efficacy - Poliana J. Demico; Isabele N. Oliveira; Vitória S. Proença-Hirata; Samuel R. Dias; Hugo A. Ghirotti; Elisangela O. Silva; Inês C. Giometti; Francis L. Pacagnelli; Kristian A. Torres-Bonilla; Stephen Hyslop; Nathália C. Galizio; Karen de Morais-Zani; et al. (Pharmaceuticals)
Background: We compared the enzymatic, coagulant, and neuromuscular activities of two variants (yellow—CDRy and white—CDRw) of Crotalus durissus ruruima venom with a sample of C. d. terrificus (CDT) venom and examined their neutralization by antivenom against CDT venom. Methods: The venoms were screened for enzymatic and coagulant activities using standard assays, and electrophoretic profiles were compared by SDS-PAGE. Neutralization was assessed by preincubating venoms with crotalic antivenom and assaying the residual activity. Results: SDS-PAGE showed that the venoms had similar electrophoretic profiles, with the main bands being phospholipase A2 (PLA2), serine proteinases, L-amino acid oxidase (LAAO), and phosphodiesterase. CDRy venom had the highest proteolytic and LAAO activities, CDRw venom had greater PLA2 and esterolytic activities at the highest quantity tested, and CDT had greater PLA2 activity than CDRy. CDRw and CDT venoms had similar proteolytic and LAAO activities, and CDRy and CDT venoms had comparable esterolytic activity. None of the venoms altered the prothrombin time (PT), but all of them decreased the activated partial thromboplastin time (aPPT); this activity was neutralized by antivenom. The minimum coagulant dose potency was CDRw >> CDRy > CDT. All venoms had thrombin-like activity that was attenuated by antivenom. CDRy and CDRw venoms showed α-fibrinogenolytic activity. All venoms partially cleaved the β-chain. CDRy and CDT venoms caused neuromuscular facilitation (enhanced muscle contractions) followed by complete blockade, whereas CDRw venom caused only blockade. Antivenom neutralized the neuromuscular activity to varying degrees. Conclusions: These findings indicate that while CDR and CDT venoms share similarities, they also differ in some enzymatic and biological activities and in neutralization by antivenom. Some of these differences could influence the clinical manifestations of envenomation by C. d. ruruima and their neutralization by the currently used therapeutic antivenom.